2014
DOI: 10.1177/0972150914535066
|View full text |Cite
|
Sign up to set email alerts
|

Entry Mode Strategies into the Brazil, Russia, India and China (BRIC) Markets

Abstract: This article explores the relevance of different entry modes for Danish exporting small and medium enterprises (SMEs). Internal and external resources that influence the choice of entry modes into the Brazil, Russia, India and China (BRIC) markets are investigated from both a resource-based view (RBV) and a market-based view (MBV). The survey conducted by the University of Southern Denmark in 2012 is based on a sample of 177 Danish SMEs. Our results of this study show that Danish companies entering the BRIC ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Brazil and South Africa have inflation targeting regimes, while China, India, and Russia operate under different frameworks. (BRICS Report, 2012) Further, China and India are the manufacturing-based economies and big importers, whereas Brazil and Russia are the huge exporters of natural resources (Ulrich, Hollensen & Boyd, 2014).…”
Section: Country-specific Pre-and Post-crisis Banking Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil and South Africa have inflation targeting regimes, while China, India, and Russia operate under different frameworks. (BRICS Report, 2012) Further, China and India are the manufacturing-based economies and big importers, whereas Brazil and Russia are the huge exporters of natural resources (Ulrich, Hollensen & Boyd, 2014).…”
Section: Country-specific Pre-and Post-crisis Banking Scenariomentioning
confidence: 99%
“…Further, China and India are the manufacturing-based economies and big importers, whereas Brazil and Russia are the huge exporters of natural resources (Ulrich, Hollensen & Boyd, 2014).…”
Section: Country-specific Pre-and Post-crisis Banking Scenariomentioning
confidence: 99%
“…When internationalizing into distant (BRIC) markets, Ulrich et al (2014) found that, control, flexibility and risk were evaluated less important internal factors than personnel and financial resources, while for external factors, the most important was market potential whereas the trade barriers, cultural distance as well as the political and economical risk are viewed as main obstacles. Other aspects such as managerial training, support policies or entrepreneurial culture of the company can also act as facilitators of that decision.…”
Section: Going International: Motivations Location and Modementioning
confidence: 99%
“…The acquiring company can be easily integrated into the strategy for the region, and could use the existing customer base on which to build. Likewise, Ulrich, Hollensen, and Boyd (), points out that this is not only to reduce the market risks, but more to establish a long‐term business network and sustain the relationship with stakeholders and agents until further decisions of expansion can be made.
A business would struggle to work in Brazil without having Brazilians involved in the strategy, who have the knowledge of the local market and the network
…”
Section: Introductionmentioning
confidence: 99%